(untitled) (MAUSAM, 2005)
A quasi-stationary synoptic system is usually seen on the weather charts during southwest monsoon period over the north-east Arabian Sea and adjoining area of Gujarat and north Konkan. The transport of absolute angular momentum, for the atmospheric weather systems, plays a significant role during the southwest monsoon period. In this paper, the mean absolute angular momentum and its vertical transport associated with MTC have been discussed. The expected accumulation of momentum throughout the troposphere upto 800 km around the centre of MTC has been calculated and displayed. The transport of angular momentum to the underlying surface and momentum loss or gain has also been discussed. Estimates have been made of surface stress by means of angular momentum transferred. The study reveals that the flux of angular momentum found to be dominated mostly between surface and 500 hPa and the values of shearing stress are positive from the centre of MTC to 500 km.